Diagnosa Penyakit Manusia Menggunakan Model Sistem Pakar - Ahmad Josi (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
Disease is a cause of disturbance in living things, disorders caused by bacteria, viruses or abnormalities of the physiological system or tissues in organs. Many ways can be done to find out the problems associated with the disease one of them by consulting to doctors, clinics and even hospitals, but the way costs are high enough, so sometimes made people suffering from disease. Many choose to keep silent while doing recovery traditional. The development of information technology is currently very supportive of provide solutions to the problem such as the development of expert system applications that can help diagnose disease and provide solutions for free.